La négociation des plaidoyers de culpabilité : une pratique hétérogène - Gravel, Sylvie (Criminologie, 1991)
This article presents the principal results of a study on plea bargaining at the Montreal Justice Hall. Various methods were adopted: observations, a thorough study of the files, interviews and analyses of the judicial statistics. The results show that negotiations vary considerably depending on the gravity of the offence concerned. In the case of a minor charge or a murder charge, the characteristics as well as the stakes and consequences of the plea bargaining are very different. In minor cases, the negotiations are reduced to their simplest form. They are a routine process of cooperation between the parties rather than bargaining to get an admission of guilt by promising the accused a reduced charge or sentence. On the contrary, the negotiations in murder cases take the traditional form of plea bargaining in which the power struggle is dominant. The study shows that it is in cases of murder than plea bargaining presents most difficulties.